Morphology Evaluation of ZrO2 Dip Coating on Mild Steel and its Corrosion Performance in NaOH Solution - M. A., Anwar; Kurniawan, Tedi; Asmara, Y. P.; W. S., Wan Harun; Oumar, A. N.; Nandyanto, A. B. D. (IOP Publishing, 2017)
In this work, the morphology of ZrO2 thin film from dip coating process on mild steel has been investigated. Mild steel was dip-coated on solution made of zirconium butoxide as a precursor, ethanol as solvent, acetylacetone as chelating agent and water for hydrolysis. Number of dipping was adjusted at 3, 5 and 7 times. The dipped sample then annealed at 350°C for two hours by adjusting the heating rate at 1°C/min respectively. The optical microscope showed that micro-cracks were observed on the surface of the coating with its concentration reduced as dipping sequence increased. The XRD result showed that annealing process can produce polycrystalline tetragonal-ZrO2. Meanwhile, SEM image showed that the thicknesses of the ZrO2 coatings were in between 400-600 nm. The corrosion resistance of uncoated and coated substrates was studied by polarization test through potentio-dynamic polarization curve at 1mV/s immersed in with 3.5% NaCl. The coating efficiency was improved as the number of layer dip coated increased, which showed improvement in corrosion protection.